Mengukur rasa syukur: Pengembangan model awal Skala Bersyukur versi Indonesia - Listiyandini, Ratih Arruum; Nathania, Andhita; Syahniar, Dessy; Sonia, Lidwina; Nadya, Rima (Konsorsium Psikologi Ilmiah Nusantara, 2015)
Feeling grateful has emotional and interpersonal advantages. When looking at suffering as something positive, person will be able to increase the ability of new coping. Development of gratitude measurement scale expected to help research, assessment, or interventions related gratitude in Indonesia population. Using non-probability accidental sampling, subjects in this research was 264 Indonesia people composed of 90 men (34%) and 174 women (66%), with age range of 20 to 75 years. Based on psychometric testing which is done through internal consistency and construct validity test, Indonesia gratitude scale seems has good reliability and validity. The scale can measure the construct consistently, can distinguish individuals with high and low gratitude, and valid to measure the gratitude construct through three factors, namely the sense of appreciation, positive feelings, and expression of gratitude. Having good psychometric standards, Indonesia gratitude scale version presented in this study can already be used to measure the gratitude in the context of research and clinical interventions in Indonesia population.